The Crisis of Painting: Benjamin, Aragon, and the Challenge of Photography - Ibarlucía, Ricardo (Aisthesis, 2025)
This essay explores Walter Benjamin’s engagement with Louis Aragon’s intellectual activity throughout the 1930s, with a particular focus on his 1936 essay Pariser Brief [II]. Malerei und Photographie. It examines Benjamin’s commentaries on Aragon’s writings within the context of the aesthetic debates surrounding Socialist Realism after the First Congress of Soviet Writers in 1934. The essay is structured in four sections. First, it discusses the decline in painting’s social and political function and how Aragon and Benjamin interpreted Gisèle Freund’s sociological analysis of the evolution of photography as an art form. The second section traces the development of collage, from Cubism to Dadaism and Surrealism, as discussed by Aragon. The third section focuses on Aragon and Benjamin’s observations on John Heartfield’s antifacist photomontages. Finally, the essay analyzes Benjamin’s interest in Antoine Wiertz’s views on painting and photography, the response of Argentine artist Antonio Berni to Aragon’s survey Où va la peinture?, and the influence of photographic techniques on Latin American muralism, particularly in the work of Mexican artist David Alfaro Siqueiros, who viewed painting as an instrument of revolutionary agitation and propaganda.